Do emojis influence social interactions? Neural and behavioral responses to affective emojis in bargaining situations. (10th January 2019) - Weiß, Martin; Gutzeit, Julian; Rodrigues, Johannes; Mussel, Patrick; Hewig, Johannes
Abstract: Emojis are nowadays a common substitute for real facial expressions to integrate emotions in social interaction. In certain contexts, emojis possibly could also transport information beyond emotions, reflecting interindividual differences or social aspects. In this study, we investigated the influence of emojis as socioemotional feedback stimuli on behavior and neural responses in a social decision game. We modified the Ultimatum Game by including emotional feedback provided by the proposer as response to the decision of the participant as receiver. Therefore, we generated identities that differed in their feedback behavior to identify differences in the processing of emotional feedback in a positive (acceptance) versus negative (rejection) frame. Regarding offer sizes, we replicated the valence effect of feedback‐related negativity for small offer sizes evoking more negative brain potentials compared to larger ones. Further, we found an effect of affective emojis on distinct ERPs: A face‐detecting neural component (N170) was examined to be a part of the processing of emojis, which resulted in significantly more negative amplitudes in response to a sad‐looking emoji compared to smiling and neutral ones. Furthermore, P3 amplitudes indicate transmission effects from the feedback emoticons to the neural processing of different offer sizes. In contrast to previous findings, P3 responses of our subjects did not depend on the offer size, but rather by which kind of partner they were made. Since some evaluative processes did not reveal any effects, emojis seem to be less effective than real facial expressions, which convey more information that is socially meaningful. Abstract : In face‐to‐face communication, information provided by facial expressions affects the social interaction itself. Nowadays, people partially transpose their ways of communication from direct conversation to messaging services. To put emphasis on the meaning of a message or to express mood, intentions, or feelings, emojis are often used. In consequence, this study aimed at investigating the influence of emojis as socioemotional feedback stimuli on behavior and neural responses in a social decision task. As a result, we found that emojis were able to influence neural processing of a certain interaction partner, whereas an impact on behavior was not found.